2022
DOI: 10.1101/2022.08.28.22279306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling the roles of trauma and genetics in psychiatric disorders using an Electronic Health Records-based approach

Abstract: Posttraumatic stress disorder (PTSD) requires an exposure to trauma for diagnosis by the DSM-V. Despite this, there is no documented linear relationship between degree of trauma and severity/chronicity of PTSD.To determine whether traumatic and stressful life events (TSLEs) collected from Electronic Health Records (EHR) interact with PTSD genetics to better define individual risk of developing PTSD. We collected trauma information from patient records in the Mount Sinai BioMe™ biobank population-based cohort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…As traumas are known to be unequally distributed across the population by race, expression was imputed separately by race and meta-analyzed together. Traumatic experiences in this cohort were defined through the EHR as described previously 67 .…”
Section: Application Of Transcriptomic Imputation Models To External ...mentioning
confidence: 99%
“…As traumas are known to be unequally distributed across the population by race, expression was imputed separately by race and meta-analyzed together. Traumatic experiences in this cohort were defined through the EHR as described previously 67 .…”
Section: Application Of Transcriptomic Imputation Models To External ...mentioning
confidence: 99%
“…The majority of psychiatric GWEIS so far have been performed in MDD, [ 116–119 ] with one additional study performed on alcohol misuse, [ 120 ] another in suicidality and posttraumatic stress, [ 121 ] and one study in PTSD. [ 87 ]…”
Section: Current Progress In Ptsd‐trauma Genetics Researchmentioning
confidence: 99%
“…The majority of psychiatric GWEIS so far have been performed in MDD, [116][117][118][119] with one additional study performed on alcohol misuse, [120] another in suicidality and posttraumatic stress, [121] and one study in PTSD. [87] Results from the GWEIS of depression indicated that SNP rs10510057 interacted with stressful life events (SLEs) and work-related stress at nominal significance; [119] rs4652467 interacted with SLEs in African Americans (AA); [118] rs12789145 and rs17070072 interacted with SLEs in individuals of European ancestry; [117] and rs10485715 (BMP2) interacted with SLEs in hospital staff. [116] In alcohol misuse, PRKG1 (variant rs1729578) significantly interacted with traumatic life experiences (TLE) in an African American cohort, and independently replicated in a secondary cohort of both African and European Americans.…”
Section: Genome-wide By Environment Interaction Studies Of Ptsdmentioning
confidence: 99%
See 2 more Smart Citations